Refractory acute retinal necrosis presenting as peripapillary choroiditis – A diagnostic and therapeutic challenge - Ankush Kawali; Sai Bhakti Mishra; Padmamalini Mahendradas; Rohit Shetty (Indian Journal of Ophthalmology)
This report describes a challenging case of refractory acute retinal necrosis (ARN) with peripapillary choroiditis as the initial presenting sign. Imaging studies confirmed multifocal choroidal lesions and noted the novel sign of vertical hyper-reflective strips (VHRS) in the outer nuclear layer. Initial treatment with acyclovir and valacyclovir failed, and involvement of the other eye suggested a resistant variant of varicella zoster virus. High-dose oral famciclovir therapy resulted in rapid resolution of ARN in both eyes. This case highlights the rare occurrence of choroiditis, the novel finding of VHRS, and the potential utility of high-dose oral famciclovir in treating refractory ARN.